The Influence of Return On Equity, Likuidity, Leverage, Activity and the Ratio of Market: Value on stock returns LQ 45 in Indonesia Stock Exchange for the period 2012-2015 - Septianingsih, Karunia Novia Ayu; Hutapea, Ganda T.; Kennedy, Posma Sariguna Johnson (Universitas Kristen Indonesia, 2017)
Objective is to see how Return On Equity, likuidity, leverage, activity and the ratio of market value partially or simultaneously against company LQ 45 stock returns in the Indonesia Stock Exchange for the period 2012-2015. Sampling this study was conducted using purposive sampling with namely sampling based criteria certain writer is used, so that the sample in this study were 17 companies LQ 45 in the Indonesia Stock Exchange for the period 2012-2015. The data source is derived from the company's financial statements for the period 2012-2015. Data analysis technique used is descriptive statistics, classical assumption test and multiple linear regression, hypothesis testing well as partial with t test and test hypotheses simultaneous with F test. t test results showed that the Return On Equity influential against stock returns, the likuidity does not affect on stock returns, leverage is not an effect on stock returns, activity no effect on stock returns, and the ratio of market value effect on stock returns. The test results F explained that the Return On Equity, likuidity, leverage, activity and the ratio of market value partially against simultaneously affect stock returns companies LQ 45 in the Indonesia Stock Exchange for the period 2012-2015.Keywords: Return On Equity, likuidity, leverage, activity, the ratio of market value, stock returns.